Home, sweet home : Gupta's real estate decision-a - Das, Prashant, (SAGE Business cases., 2024)
A salaried, upper-middle class couple in its 40’s is deciding whether to buy or build their home near their hometown or away from the city where they work. As such, this is a question of real estate budget estimates. They collect relevant market data and assess the financial feasibility of their homebuilding (or purchase). The mini-case provides a systematic approach to the classical real estate decision of households: How much will it cost to build their dream home and buy a land parcel for the purpose? Subjective and quantitative aspects are considered to decide on a land parcel, size of the home and estimate the construction cost. The main decision-point is: Is it feasible to build a home from scratch (against buying a condominium unit) given the couple’s budget and social stratum? There are two case studies with the same name but different suffices (A and B). The (mini-) case A could be clubbed with the more analytical case B. The analysis and decision for this case are relatively basic, and more suited for undergraduate courses, if conducted in isolation. As such, this case could also be taught independently aiming at cost estimation for building a home. However, the notes provided in this document could be used to carry some technical discussions and include the case in senior or masters-level courses as well.